2023
DOI: 10.1002/ejoc.202300176
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorescent 2‐Aminopurine Derivatives: Synthesis, Photo‐physical Characterization, and Preliminary Cytotoxicity Evaluation

Abstract: New fluorescent nucleobase analogues (FBAs) are emerging as extraordinarily useful tools for DNA labelling technologies. The highly fluorescent adenine analogue 2-aminopurine (2AP) is still the most used within the few hundreds of newly FBAs synthesized, but its excitation in the UV region demands for high energy sources endangering living cells. New and highly fluorescent 2AP derivatives, 2-amino-6-cyanopurines, were obtained using simpler but efficient synthesis method. All the new compounds exhibit advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…In a recently reported work, 25 the preparation of N -cyanoimidoylcyanides 1 was achieved from 5-amino-4-cyanoformimidoylimidazole by an addition reaction of cyanamide to these precursors followed by elimination of ammonia. In that study, N -cyanoimidoylcyanides 1 were then converted to highly fluorescent 2-amino-6-cyanopurines through an intramolecular cyclization that involves a nucleophilic attack of the 5-amino group on the cyanoimino unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently reported work, 25 the preparation of N -cyanoimidoylcyanides 1 was achieved from 5-amino-4-cyanoformimidoylimidazole by an addition reaction of cyanamide to these precursors followed by elimination of ammonia. In that study, N -cyanoimidoylcyanides 1 were then converted to highly fluorescent 2-amino-6-cyanopurines through an intramolecular cyclization that involves a nucleophilic attack of the 5-amino group on the cyanoimino unit.…”
Section: Resultsmentioning
confidence: 99%
“…The imidazole precursors 1 , the N -cyanoimidoylcyanides, were prepared according to a recently reported method. 25 Intermediate compounds 2 were not easy to isolate because they are highly soluble in reaction solvents. So, only a few compounds 2 could be fully characterized.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, highly fluorescent 2-amino-6-cyanopurines 2 were synthesized through condensation reactions of imidazole precursors with cyanamide, followed by cyclization of key intermediates 1 (Scheme 1). 23 Aiming to generate new fluorescent analogues, the reactivity of this new purine scaffold was investigated. Attempts to modify the 6-cyano group revealed that purines 2 with 9-aryl substituents undergo ring-opening of the imidazole moiety upon heating in acidic media, which generates new N 4 -substituted 2,4,5-triaminopyrimidines 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A, T (U), C, and G are building blocks of nucleic acids and are very weakly fluorescent . In order to probe the structure and dynamics of DNA and RNA sequences and their interaction with other biological molecules, structural nucleobase analogues have been developed with high-emission quantum yields. These structural analogues are called fluorescent nucleic acid base analogues (FBAs). A summary of recent developments in the field of FBAs can be found in these articles. Two of the oldest known fluorescent base analogues are 2-aminopurine (2AP) and ethenoadenine (εA), both of which are fluorescent analogues of adenine.…”
Section: Introductionmentioning
confidence: 99%